2001
DOI: 10.1034/j.1399-3011.2001.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogs

Abstract: Somatostatin is a hypothalamic peptide hormone that inhibits the secretion of growth hormone, glucagon, insulin, gastrin and secretin, and also plays a role in neural transmission. Because of its wide range of possible clinical applications hundreds of somatostatin analogs have been synthesized and bioassayed to date. This review gives a historical perspective, summarizing approximately 30 years of research on somatostatin. The main focus is on the structure-activity relationships and conformational studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 106 publications
3
95
0
1
Order By: Relevance
“…5 The successful use of radiolabelled somatostatin for imaging and radionuclide therapy has prompted the development of new cyclic and acyclic analogues with better receptor affinity and higher stability under physiological conditions. 6 Octreotide, 7 1 (Chart 1), a metabolically-stabilized cycloctapeptide analogue of somatostatin that includes D-amino acids to enhance resistance to enzymatic degradation and a cystine bridge to stabilize the pharmacophore β-turn, is particularly interesting because of its high affinity and selectivity for the receptor sst 2 octreotide which are used in the clinics for molecular imaging and therapy of neuroendocrine tumors, respectively. 8 Octreotide has also been conjugated to cytotoxic organic compounds such as doxorubicin, camptothecin and paclitaxel, with promising results in some cases because of the reduced toxicity and the increased selectivity of the conjugates compared with that of the free drug.…”
Section: Introductionmentioning
confidence: 99%
“…5 The successful use of radiolabelled somatostatin for imaging and radionuclide therapy has prompted the development of new cyclic and acyclic analogues with better receptor affinity and higher stability under physiological conditions. 6 Octreotide, 7 1 (Chart 1), a metabolically-stabilized cycloctapeptide analogue of somatostatin that includes D-amino acids to enhance resistance to enzymatic degradation and a cystine bridge to stabilize the pharmacophore β-turn, is particularly interesting because of its high affinity and selectivity for the receptor sst 2 octreotide which are used in the clinics for molecular imaging and therapy of neuroendocrine tumors, respectively. 8 Octreotide has also been conjugated to cytotoxic organic compounds such as doxorubicin, camptothecin and paclitaxel, with promising results in some cases because of the reduced toxicity and the increased selectivity of the conjugates compared with that of the free drug.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the disulfide bridge in U-II would act in a similar manner. Structure-activity relationship (SAR) studies of SST already showed that these pharmacophoric features are essential for the SST biological activity (Janecka et al, 2001). Furthermore, previous fish U-II (Itoh et al, 1987) and human U-II (Kinney et al, 2001(Kinney et al, , 2002Flohr et al, 2002) SAR studies showed that the highly conserved C-terminal segment CF-WKYCV is the minimal sequence required to maintain a high potency and that Lys-8 appeared as an important residue for U-II activity (Carmada et al, 2002).…”
mentioning
confidence: 99%
“…Such ''hits'' have not been easy to find for the galanin receptors (9), and the two low-affinity compounds that were found were not chemically tractable. Although most neuropeptide-receptor ligands that have reached clinical use are antagonists (32), some neuropeptide-receptor agonists have been developed from peptidomimetics, most often for cyclic peptide ligands such as somatostatinreceptor agonists (33). In the case of galanin receptors, a tripeptide mimetic library based on the pharmacophores of galanin yielded the compound galnon, which, despite its low affinity and poor receptor-subtype selectivity, has rapidly become a tool in our studies on the role of galanin in seizures, cognition, pain, feeding, and opiate withdrawal (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%